ОСНОВНЫЕ МЕТОДОЛОГИЧЕСКИЕ ПАРАДИГМЫ ТЕОРИИ РАССЕЛЕНИЯ НАСЕЛЕНИЯ - Гали, Д Е (Journal of Economic Research & Business Administration, 2015)
In this article, a comparative analysis of paradigms in the theory of population settlement. Disclosed the concept of "resettlement". You are the revealed specific features and factors paradigms of population settlement. The definitions of researchers on the theory of resettlement on the basis of consideration of a proposed new scientific interpretation of the definition of resettlement of the population.